Expression of mesothelin in thymic carcinoma and its potential therapeutic significance. (November 2016) - Thomas, Anish; Chen, Yuanbin; Berman, Arlene; Schrump, David S.; Giaccone, Giuseppe; Pastan, Ira; Venzon, David J.; Liewehr, David J.; Steinberg, Seth M.; Miettinen, Markku; Hassan, Raffit; Rajan, Arun
Highlights: Mesothelin, a cell surface antigen is a target for tumor-directed therapy. Thymic carcinomas frequently demonstrate strong mesothelin expression. High mesothelin expression in thymic carcinoma is associated with longer survival. Mesothelin-directed therapy should be evaluated in advanced thymic carcinoma. Abstract: Objectives: Advanced thymic epithelial tumors (TETs) lack adequate treatment options in part due to absence of well characterized tumor-specific antigens. Mesothelin, a cell surface antigen, has been used successfully as a target for tumor-directed therapy. We sought to determine tumor expression and serum levels of mesothelin in patients with TETs. Patients and methods: Tissue samples were obtained from 71 patients with histologically confirmed, unresectable advanced TETs and evaluated for mesothelin expression by immunohistochemistry. The evaluation was blinded for clinical data and outcome. Mesothelin expression and its association with clinico-pathological parameters and survival were assessed. Results: Thymic carcinoma, thymoma, and thymic neuroendocrine tumors (NETs) accounted for 34 (48%), 29 (41%), and 8 (11%) cases respectively. Mesothelin expression was seen in a significantly larger proportion of thymic carcinoma (27/34, 79%) than thymoma (3/29, 10%) (P < 0.0001) and was absent in thymic NETs. Among thymic carcinomas 13/34 (38%) showed expression in nearly all tumor cells. Immunoreactivity was membranous, strong, and homogenous. Patients with thymic carcinoma and high mesothelin expression (in >50% of tumor cells) had significantly improved overall survival (median not reached, n = 19) compared to patients with no or low mesothelin expression (1.60 years; 95% CI: 1.24–4.94 years; n = 15; HR = 4.46, 95% CI: 1.55–12.80; p = 0.0026). Conclusion: Mesothelin expression is frequently observed in advanced thymic carcinomas, infrequently in thymomas and is absent in thymic NETs. Due to strong, membranous expression mesothelin is a potential therapeutic target in thymic carcinoma.